Szubjektív források a Horthy-korszakra vonatkozó memoárirodalom vizsgálatának néhány tanulsága - Pihurik Judit (University of Szeged, Magyar Medievisztikai Kutatócsoport Szeged, 1995)
After 1945 diaries, memoires, memorial papers relating to the Horthy-era were published in Hungary and abroad as well. From the second part of the 1980's onwards their number grew steadily, hitherto unknown memories and ones written by emigrants were published in Hungary. The historical value of these special narrative sources can be questioned because of several considerations. However, in the background of self-justifying bias and subjective viewpoint, the age and the individual adjusting himself to the ever changing contemporary expectations always emerge. The variety of viewpoints makes it possible to establish a more accurate picture of the age, the errors, the misinterpretations and disproportionate descriptions and other problematical features can be corrected by comparing the memoires to historical evidence contained in source publications and to results of research. A comparison of the statements of contemporaries can also yield invaluable insights. This study undertook a brief review of those considerations which define evaluation and thematic grouping of memoires of the Horthy-era.
Keywords: Bölcsészettudományok; Történettudomány és régészet